PEMENUHAN HAK KONSUMEN ATAS INFORMASI PRODUK CAIRAN ROKOK ELEKTRIK (E-JUICE) DI BUKITTINGGI - Febri Yanda Saputra; Benny Rusli; Syuryani Syuryani (Ensiklopedia of Journal, 2023)
Smoking is no longer a taboo subject among Indonesian people, ranging from children, teenagers, adults to the elderly can freely use cigarettes. Along with the development of technology, a new product emerged called electric cigarette. The sale of liquids is becoming more and more promising in the business world, because there are so many enthusiasts for this liquid, the marketing of liquids is increasing day by day. However, the liquid in the market does not receive supervision from the Food and Drug Supervisory Agency (BPOM), as evidenced by the large number of electronic cigarettes or liquids that are sold freely without a clear expiration date. This of course will endanger consumers who use the liquid in the long term even though there is already Law Number 8 of 1999 concerning Consumer Protection, namely the obligation of business actors to provide correct, clear and honest information regarding the conditions and guarantees of goods and/or services and be.